The Covenant Quarterly (Online) - North Park Theological Seminary; Evangelical Covenant Church (Chicago, Ilinois : Covenant Publications., 1941)
"... the ministerial journal of the Evangelical Covenant Church. Published by Covenant Publications through North Park Theological Seminary, the Quarterly seeks to foster theological reflection on ministerial praxis in service to ECC pastors and the broader church."
Text (electronic journal).
Keywords: Evangelical Covenant Church -- Periodicals; Evangelical Covenant Church; Theology -- Periodicals; Electronic journals